High-impact-resistant ABS plastic shell material and preparation method thereof

CN122978638APending Publication Date: 2026-10-27GUIZHOU HAOYANG NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611138882.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

本发明通过环氧官能化核壳增韧剂、离聚物与表面氨基化纳米二氧化硅之间的原位化学反应,成功构筑了以核壳橡胶粒子为中心的离子-共价杂化交联网络。该网络在受到外力冲击时,可同时激活橡胶相空洞化、离子簇可逆牺牲键解离与重组、交联网络链段高弹性形变以及纳米粒子诱导基体剪切屈服等多重能量耗散机制,使材料的悬臂梁缺口冲击强度大幅提升。更为突出的是,该杂化交联网络在低温下仍能保持高效的应力传递与能量耗散能力,-30℃低温冲击强度保持率高,有效解决了常规增韧ABS材料低温脆化的技术瓶颈,可满足严寒环境或高载荷冲击等严苛应用场景的使用要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of high impact resistance ABS plastic shell materials and preparation method thereof.The material is made of ABS resin 50~75 parts, epoxy functionalized core-shell structure toughening agent 15~30 parts, ionomer 3~8 parts, surface aminated nanosilica 1~5 parts, compatibilizer 1~3 parts, antioxidant 0.2~0.5 parts and lubricant 0.3~0.8 parts.The toughening agent is crosslinked polybutadiene as core, styrene-acrylonitrile-glycidyl methacrylate terpolymer as shell.In the process of melt extrusion, shell layer epoxy group and ionomer carboxyl, nanosilica surface amino occur in-situ chemical reaction, build ion-covalent hybrid crosslinking network with core-shell rubber particles as center.The design breaks the rigid-flexible balance limit of traditional physical blending, the obtained material cantilever beam notched impact strength reaches 55~75 kJ / m², tensile strength ≥45MPa, flexural modulus ≥2100MPa, and has excellent chemical stress cracking resistance and good processing performance, suitable for electric appliance shell, automotive interior and exterior trim parts and other plastic shell products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, specifically relating to a high-impact acrylonitrile-butadiene-styrene (ABS) plastic shell material and its preparation method. Background Technology ABS resin is widely used in the plastic housing industry for electrical appliances, automotive interior and exterior parts, and daily necessities due to its good mechanical properties, processing fluidity, and surface gloss. With the development of products becoming thinner and lighter and more complex in application, higher requirements are being placed on the impact resistance of ABS plastic housing materials, especially low-temperature impact resistance and chemical stress cracking resistance.

[0002] Currently, the conventional methods to improve the impact resistance of ABS materials mainly include: 1) Increasing the rubber content in ABS graft copolymers. Increasing the rubber phase content can improve notched impact strength, but it often leads to a significant decrease in tensile strength, flexural modulus, and surface hardness, failing to meet the requirements of plastic shells for rigidity and scratch resistance. 2) Alloying with high-performance resins such as polycarbonate. PC / ABS alloys have excellent rigidity-toughness balance and low-temperature toughness, but the cost is high, and they are sensitive to molding and processing techniques. The products are prone to internal stress, which can induce solvent cracking. 3) Adding toughening agents, such as high-rubber powder and MBS core-shell particles. However, physically blended toughening agents are only combined with the matrix by van der Waals forces or limited interfacial entanglement, which limits the toughening efficiency. Uneven dispersion can also easily cause surface defects. At the same time, adding large amounts of low-modulus toughening agents to achieve ultra-high impact resistance also sacrifices rigidity, heat resistance, and chemical resistance.

[0003] Some publicly available patents attempt to combine nanoparticles with toughening agents, such as CN108219361A, which discloses a high-impact ABS material containing high-polymer powder and nano-calcium carbonate. However, due to the tendency of inorganic nanoparticles to aggregate and the lack of strong interfacial chemical bonds, the energy dissipation mechanism is still mainly matrix creasing and cavitation. Under repeated impacts or low-temperature conditions, creasing is prone to expand into cracks, resulting in limited toughening effect and the fundamental problem of rigidity versus toughness remains unresolved.

[0004] Therefore, how to break through the "rigid-toughness" balance limit of traditional physical blending, and achieve a synergistic improvement in ultra-high impact resistance and environmental stress cracking resistance while maintaining the required rigidity and surface quality of ABS plastic shells, is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] The purpose of this invention is to provide a high-impact ABS plastic shell material. This material forms an ion-covalent hybrid crosslinked network centered on core-shell rubber particles in situ during the melt processing of a specific reactive component, thereby endowing the material with ultra-high impact strength while maintaining excellent rigidity and resistance to chemical stress cracking.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a high-impact ABS plastic shell material, which is made of components comprising the following parts by weight: ABS resin: 50-75 parts Epoxy functionalized core-shell toughening agent: 15-30 parts Ionomer: 3-8 parts Surface-aminated nano-silica: 1-5 parts Compatibilizer: 1-3 parts Antioxidant: 0.2~0.5 parts Lubricant: 0.3~0.8 parts The epoxy-functionalized core-shell toughening agent uses cross-linked polybutadiene as the core and styrene-acrylonitrile-glycidyl methacrylate (St-AN-GMA) terpolymer as the shell. The epoxy groups in the shell are derived from glycidyl methacrylate (GMA) and serve as active reaction sites.

[0007] The ionomer is a zinc or sodium salt of ethylene-methacrylic acid copolymer, preferably a zinc salt of ethylene-methacrylic acid copolymer. The ionomer molecular chain contains both unneutralized carboxyl groups (-COOH) and ionic clusters.

[0008] The surface-aminated nano-silica is prepared by surface treatment of nano-silica with aminosilane coupling agents such as γ-aminopropyltriethoxysilane (KH-550), and its surface has active amino groups (-NH2).

[0009] The compatibilizer is a styrene-acrylonitrile-maleic anhydride copolymer (SAN-g-MAH), with a grafting rate preferably of 1.5 to 2.5%.

[0010] In this invention, the epoxy groups in the shell of the epoxy-functionalized core-shell toughening agent undergo a ring-opening reaction with the carboxyl groups in the ionomer during melt extrusion to form ester bonds, while simultaneously undergoing a nucleophilic addition reaction with the amino groups on the surface of nano-silica. Thus, with the core-shell rubber particles at the center, flexible ionomer segments are chemically linked to rigid nano-silica particles through covalent and ionic crosslinking bonds, constructing a unique ion-covalent hybrid crosslinking network in situ within the ABS matrix.

[0011] When subjected to external impact, this network can dissipate energy through multiple mechanisms: rubber voiding and debonding of the cross-linked polybutadiene core; breaking and rearranging of chemical bonds at the shell interface; high elastic deformation of hybrid cross-linked network segments; dissociation and recombination of ion clusters; and matrix shear yielding induced by nano-silica. This multi-scale synergistic toughening mechanism greatly improves the absorption and dissipation efficiency of impact energy, breaking through the limits of conventional toughening systems. Simultaneously, the reinforcing effect of the cross-linked network and nanoparticles ensures the material's high rigidity and strength; the cross-linked structure effectively constrains molecular chain movement, endowing the material with excellent resistance to environmental stress cracking. Furthermore, the ionic cross-linking of the ionomer exhibits certain fluidity and dynamic reversibility at processing temperatures, ensuring the material maintains its thermoplastic processability.

[0012] Secondly, the present invention provides a method for preparing the above-mentioned high-impact ABS plastic shell material, comprising the following steps: (1) After drying the ABS resin, add it to a high-speed mixer in proportion with epoxy functionalized core-shell toughening agent, ionomer, surface aminated nano silica, compatibilizer, antioxidant and lubricant, and mix evenly to obtain a premix. (2) The premixed material is fed into a twin-screw extruder and melt-blended, extruded, and granulated at a temperature of 190~230℃ and a screw speed of 250~400rpm to obtain the high-impact ABS plastic shell material. During this process, the reactive groups undergo in-situ chemical reactions to construct the hybrid crosslinked network.

[0013] Preferably, the temperature of each zone of the twin-screw extruder is set as follows: Zone 1 190~200℃, Zone 2 205~215℃, Zone 3 215~225℃, Zone 4 220~230℃, Zone 5 220~230℃, and the die head 215~225℃.

[0014] By adopting the above technical solution, the present invention has the following beneficial effects: This invention successfully constructs an ion-covalent hybrid crosslinking network centered on core-shell rubber particles through an in-situ chemical reaction between an epoxy-functionalized core-shell toughening agent, an ionomer, and surface-aminated nano-silica. Upon impact, this network simultaneously activates multiple energy dissipation mechanisms, including rubber phase voiding, reversible sacrificial bond dissociation and recombination of ion clusters, highly elastic deformation of crosslinked network segments, and nanoparticle-induced matrix shear yielding, significantly enhancing the cantilever beam notched impact strength of the material. More notably, this hybrid crosslinking network maintains efficient stress transfer and energy dissipation capabilities at low temperatures, exhibiting high impact strength retention at -30°C. This effectively solves the technical bottleneck of low-temperature embrittlement in conventional toughened ABS materials, meeting the requirements of demanding applications such as frigid environments or high-load impacts.

[0015] This invention avoids the problem of a sharp drop in rigidity caused by the addition of large amounts of low-modulus rubber phases or flexible toughening agents in traditional toughening methods in pursuit of high impact resistance. On the one hand, the covalent cross-linking bonds and ion clusters in the hybrid cross-linking network effectively constrain the movement of molecular chains, endowing the material with high bulk strength; on the other hand, the surface-aminated nano-silica acts as uniformly dispersed rigidity-enhancing points and is anchored in the cross-linking network through chemical bonds, playing a significant reinforcing role. Therefore, the material of this invention achieves ultra-high impact resistance while maintaining a tensile strength of not less than 45 MPa and a flexural modulus of not less than 2100 MPa, providing sufficient supporting stiffness and dimensional stability for plastic shell products such as electrical appliance housings and automotive interior and exterior parts, achieving a high balance between rigidity and toughness. In terms of chemical stress cracking resistance, the three-dimensional hybrid cross-linking network constructed in this invention effectively constrains the movement, relaxation, and slippage of ABS molecular chains under the action of solvents or chemical media, essentially inhibiting the initiation and propagation of solvent-induced microcracks. Detailed Implementation

[0016] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0017] Preparation Example 1: Preparation of epoxy functionalized core-shell toughening agent Add 2000g of deionized water, 1200g of cross-linked polybutadiene latex (55% solid content, average particle size 280nm), and 15g of disproportionated rosin acid potassium soap to a reactor. Under nitrogen protection, stir and heat to 65℃. Mix 390g of styrene, 150g of acrylonitrile, and 90g of glycidyl methacrylate (GMA) thoroughly to prepare the shell monomer mixture. Add the shell monomer mixture dropwise to the reactor, simultaneously adding an initiator solution consisting of 4g of potassium persulfate and 200g of deionized water over a period of 3 hours. After the addition is complete, add another initiator solution consisting of 0.5g of potassium persulfate and 50g of deionized water, and continue the reaction at 70℃ for 1 hour. Cool and discharge the material. After demulsification, washing, and drying, the epoxy functionalized core-shell toughening agent is obtained.

[0018] Example 1 650g of ABS resin was dried at 80℃ for 4 hours, cooled, and then fed into a high-speed mixer. The following were added sequentially: 250g of the epoxy functionalized core-shell toughening agent obtained in Preparation Example 1 above; 60g of zinc salt of ethylene-methacrylic acid copolymer; 30g of surface-aminated nano-silica (average particle size 20nm, KH-550 treated, amino grafting amount 2.5wt%); 20g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%); 3g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1); and 5g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder, with temperatures from zone one to the die head of 195℃, 210℃, 220℃, 225℃, 225℃, and 220℃ respectively, and a screw speed of 350rpm. The mixture was melt-extruded, cooled, and pelletized to obtain the high-impact ABS plastic shell material. The granules were injection molded into standard samples for performance testing.

[0019] Example 2 750g of ABS resin was dried at 80℃ for 4 hours, cooled, and then fed into a high-speed mixer. The following were added sequentially: 150g of the epoxy functionalized core-shell toughening agent obtained in Preparation Example 1, 30g of zinc salt of ethylene-methacrylic acid copolymer, 10g of surface-aminated nano-silica (average particle size 20nm, KH-550 treated, amino grafting amount 2.5wt%), 10g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%), 2g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1), and 3g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder, with temperatures from zone one to the die head of 190℃, 205℃, 215℃, 220℃, 220℃, and 215℃ respectively, and a screw speed of 250rpm. The mixture was melt-extruded, cooled, and pelletized to obtain the high-impact ABS plastic shell material. The granules were injection molded into standard samples for performance testing.

[0020] Example 3 500g of ABS resin was dried at 80℃ for 4 hours, cooled, and then fed into a high-speed mixer. The following were added sequentially: 300g of the epoxy functionalized core-shell toughening agent obtained in Preparation Example 1, 80g of zinc salt of ethylene-methacrylic acid copolymer, 50g of surface-aminated nano-silica (average particle size 20nm, KH-550 treated, amino grafting amount 2.5wt%), 30g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%), 5g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1), and 8g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder, with temperatures from zone one to the die head of 200℃, 215℃, 225℃, 230℃, 230℃, and 225℃ respectively, and a screw speed of 400rpm. The mixture was melt-extruded, cooled, and pelletized to obtain the high-impact ABS plastic shell material. The granules were injection molded into standard samples for performance testing.

[0021] Example 4 700g of ABS resin was dried at 80℃ for 4 hours, cooled, and then fed into a high-speed mixer. The following were added sequentially: 180g of the epoxy functionalized core-shell toughening agent obtained in Preparation Example 1, 50g of zinc salt of ethylene-methacrylic acid copolymer, 20g of surface-aminated nano-silica (average particle size 20nm, KH-550 treated, amino grafting amount 2.5wt%), 15g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%), 3g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1), and 5g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder, with temperatures from zone one to the die head of 190℃, 205℃, 215℃, 220℃, 220℃, and 215℃ respectively, and a screw speed of 300rpm. The mixture was melt-extruded, cooled, and pelletized to obtain the high-impact ABS plastic shell material. The granules were injection molded into standard samples for performance testing.

[0022] Example 5 550g of ABS resin was dried at 80℃ for 4 hours, cooled, and then fed into a high-speed mixer. The following were added sequentially: 280g of the epoxy functionalized core-shell toughening agent obtained in Preparation Example 1, 70g of zinc salt of ethylene-methacrylic acid copolymer, 40g of surface-aminated nano-silica (average particle size 20nm, KH-550 treated, amino grafting amount 2.5wt%), 25g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%), 4g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1), and 7g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder, with temperatures from zone one to the die head of 200℃, 215℃, 225℃, 230℃, 230℃, and 225℃ respectively, and a screw speed of 380rpm. The mixture was melt-extruded, cooled, and pelletized to obtain the high-impact ABS plastic shell material. The granules were injection molded into standard samples for performance testing.

[0023] Example 6 600g of ABS resin was dried at 80℃ for 4 hours, cooled, and then fed into a high-speed mixer. The following were added sequentially: 220g of the epoxy functionalized core-shell toughening agent obtained in Preparation Example 1, 40g of zinc salt of ethylene-methacrylic acid copolymer, 25g of surface-aminated nano-silica (average particle size 20nm, KH-550 treated, amino grafting amount 2.5wt%), 18g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%), 3g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1), and 5g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder, with temperatures from zone one to the die head of 195℃, 210℃, 220℃, 225℃, 225℃, and 220℃ respectively, and a screw speed of 320rpm. The mixture was melt-extruded, cooled, and pelletized to obtain the high-impact ABS plastic shell material. The granules were injection molded into standard samples for performance testing.

[0024] Comparative Example 1 1000g of ABS resin was dried at 80℃ for 4 hours and then fed into a twin-screw extruder. The temperatures from zone one to the die head were 195℃, 210℃, 220℃, 225℃, 225℃, and 220℃ respectively, with a screw speed of 350rpm. The resin was melt-extruded, cooled, and pelletized. The pellets were then injection-molded into standard samples for performance testing.

[0025] Comparative Example 2 650g of ABS resin was dried at 80℃ for 4 hours, cooled, and then added to a high-speed mixer. The following were added sequentially: 250g of non-reactive MBS core-shell particles (shell without GMA), 60g of zinc salt of ethylene-methacrylic acid copolymer, 30g of surface-aminated nano-silica (average particle size 20nm, KH-550 treated, amino grafting amount 2.5wt%), 20g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%), 3g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1), and 5g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder with temperatures from zone one to the die head of 195℃, 210℃, 220℃, 225℃, 225℃, and 220℃ respectively, at a screw speed of 350rpm. The mixture was melt-extruded, cooled, and pelletized. The pellets were injection molded into standard samples for performance testing.

[0026] Comparative Example 3 650g of ABS resin was dried at 80℃ for 4 hours, cooled, and then fed into a high-speed mixer. The following were added sequentially: 250g of the epoxy functionalized core-shell toughening agent obtained in Preparation Example 1; 30g of surface-aminated nano-silica (average particle size 20nm, KH-550 treated, amino grafting amount 2.5wt%); 20g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%); 3g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1); and 5g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder, with temperatures from zone one to the die head of 195℃, 210℃, 220℃, 225℃, 225℃, and 220℃ respectively, and a screw speed of 350rpm. The mixture was melt-extruded, cooled, and pelletized. The pellets were injection molded into standard samples for performance testing.

[0027] Comparative Example 4 650g of ABS resin was dried at 80℃ for 4 hours, cooled, and then fed into a high-speed mixer. The following were added sequentially: 250g of the epoxy functionalized core-shell toughening agent obtained in Preparation Example 1, 60g of zinc salt of ethylene-methacrylic acid copolymer, 20g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%), 3g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1), and 5g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder, with temperatures from zone one to the die head of 195℃, 210℃, 220℃, 225℃, 225℃, and 220℃ respectively, and a screw speed of 350 rpm. The mixture was melt-extruded, cooled, and pelletized. The pellets were injection molded into standard samples for performance testing.

[0028] Comparative Example 5 650g of ABS resin was dried at 80℃ for 4 hours, cooled, and then fed into a high-speed mixer. The following were added sequentially: 100g of the epoxy functionalized core-shell toughening agent obtained in Preparation Example 1, 60g of zinc salt of ethylene-methacrylic acid copolymer, 30g of surface-aminated nano-silica (average particle size 20nm, KH-550 treated, amino grafting amount 2.5wt%), 20g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%), 3g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1), and 5g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder, with temperatures from zone one to the die head of 195℃, 210℃, 220℃, 225℃, 225℃, and 220℃ respectively, and a screw speed of 350rpm. The mixture was melt-extruded, cooled, and pelletized. The pellets were injection molded into standard samples for performance testing.

[0029] Comparative Example 6 650g of ABS resin was dried at 80℃ for 4 hours, cooled, and then fed into a high-speed mixer. The following were added sequentially: 250g of the epoxy functionalized core-shell toughening agent obtained in Preparation Example 1, 100g of zinc salt of ethylene-methacrylic acid copolymer, 30g of surface-aminated nano-silica (average particle size 20nm, KH-550 treated, amino grafting amount 2.5wt%), 20g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%), 3g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1), and 5g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder, with temperatures from zone one to the die head of 195℃, 210℃, 220℃, 225℃, 225℃, and 220℃ respectively, and a screw speed of 350rpm. The mixture was melt-extruded, cooled, and pelletized. The pellets were injection molded into standard samples for performance testing.

[0030] Comparative Example 7 650g of ABS resin was dried at 80℃ for 4 hours, cooled, and then fed into a high-speed mixer. The following were added sequentially: 250g of the epoxy functionalized core-shell toughening agent obtained in Preparation Example 1, 60g of zinc salt of ethylene-methacrylic acid copolymer, 5g of surface-aminated nano-silica (average particle size 20nm, KH-550 treated, amino grafting amount 2.5wt%), 20g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%), 3g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1), and 5g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder, with temperatures from zone one to the die head of 195℃, 210℃, 220℃, 225℃, 225℃, and 220℃ respectively, and a screw speed of 350rpm. The mixture was melt-extruded, cooled, and pelletized. The pellets were injection molded into standard samples for performance testing.

[0031] Comparative Example 8 650g of ABS resin was dried at 80℃ for 4 hours, cooled, and then fed into a high-speed mixer. The following were added sequentially: 250g of the epoxy functionalized core-shell toughening agent obtained in Preparation Example 1, 60g of zinc salt of ethylene-methacrylic acid copolymer, 70g of surface-aminated nano-silica (average particle size 20nm, KH-550 treated, amino grafting amount 2.5wt%), 20g of styrene-acrylonitrile-maleic anhydride copolymer (grafting rate 2.0%), 3g of antioxidant (1010 and 168 compounded at a mass ratio of 1:1), and 5g of ethylene bis-stearamide. The mixer was turned on and stirred for 5 minutes until homogeneous, yielding a premix. The premix was added to a twin-screw extruder, with temperatures from zone one to the die head of 195℃, 210℃, 220℃, 225℃, 225℃, and 220℃ respectively, and a screw speed of 350rpm. The mixture was melt-extruded, cooled, and pelletized. The pellets were injection molded into standard samples for performance testing.

[0032] The performance test results of each embodiment and comparative example are summarized in Table 1.

[0033] Table 1 Performance test results of each embodiment and comparative example

[0034] As shown in Table 1, the embodiments of this application (Examples 1-6) constructed an ion-covalent hybrid crosslinking network through in-situ chemical reaction between epoxy functionalized core-shell toughening agent, ionomer, and surface-aminated nano-silica. All achieved ultra-high notched impact strength of 55-75 kJ / m² while maintaining tensile strength ≥45 MPa and flexural modulus ≥2100 MPa, exhibiting excellent low-temperature impact strength and outstanding resistance to chemical stress cracking. Comparative Example 1, using pure ABS resin, had a notched impact strength of only 22 kJ / m² and cracked severely after immersion. Comparative Example 2 used non-reactive MBS core-shell particles without GMA to replace the epoxy functionalized toughening agent; due to the inability to form a chemically bonded network, the impact strength was only 38 kJ / m², with a significant decrease in rigidity and chemical resistance. Comparative Example 3 lacked ionomer, and Comparative Example 4 lacked aminated nano-silica; both failed to form a complete hybrid crosslinking network, resulting in impact strengths of 49 kJ / m² and 52 kJ / m², respectively, and poorer crack resistance. Comparative Example 5, with only 100g of toughening agent, showed insufficient cross-linking network density and limited toughening effect. Comparative Example 6, with 100g of ionomer, resulted in a significant loss of material rigidity. Comparative Examples 7 and 8 either showed a decrease in toughening effect or a deterioration in the rigidity-toughness balance. The above comparative examples fully demonstrate the unique chemical synergistic effect among the components of this invention, as well as the rationality and necessity of limiting the dosage range of each component.

[0035] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-impact ABS plastic shell material, characterized in that, It is made from the following components in parts by weight: ABS resin: 50-75 parts; Epoxy functionalized core-shell toughening agent: 15-30 parts; Ionomer: 3-8 parts; Surface-aminated nano-silica: 1-5 parts; Compatibilizer: 1-3 parts; Antioxidant: 0.2~0.5 parts; Lubricant: 0.3~0.8 parts; The epoxy functionalized core-shell toughening agent has cross-linked polybutadiene as the core and styrene-acrylonitrile-glycidyl methacrylate terpolymer as the shell; the ionomer is a metal salt of ethylene-methacrylic acid copolymer; and the surface-aminated nano silica is nano silica with active amino groups on its surface after treatment with an aminosilane coupling agent.

2. The high impact-resistant ABS plastic shell material according to claim 1, characterized in that: The ionomer is a zinc or sodium salt of an ethylene-methacrylic acid copolymer.

3. The high impact-resistant ABS plastic shell material according to claim 2, characterized in that: The ionomer molecular chain contains both unneutralized carboxyl groups and ionic clusters.

4. The high impact-resistant ABS plastic shell material according to claim 1, characterized in that: The surface-aminated nano-silica is prepared by surface treatment of nano-silica with γ-aminopropyltriethoxysilane.

5. The high impact-resistant ABS plastic shell material according to claim 4, characterized in that: The surface amino grafting amount of the surface-aminated nano silica is 1.5~3.0wt%, and the average particle size is 15~50nm.

6. The high impact-resistant ABS plastic shell material according to claim 1, characterized in that: The core-shell mass ratio of the epoxy functionalized core-shell toughening agent is 55 / 45 to 70 / 30, and the content of glycidyl methacrylate monomer in the shell terpolymer accounts for 8 to 20% of the shell mass.

7. The high impact-resistant ABS plastic shell material according to claim 1, characterized in that: The compatibilizer is a styrene-acrylonitrile-maleic anhydride copolymer with a grafting rate of 1.5~2.5%.

8. The method for preparing the high impact-resistant ABS plastic shell material according to any one of claims 1 to 7, characterized in that, Includes the following steps: (1) The dried ABS resin is mixed with the epoxy functionalized core-shell toughening agent, ionomer, surface aminated nano silica, compatibilizer, antioxidant and lubricant in proportion to obtain a premix; (2) The premixed material is fed into a twin-screw extruder and melt-blended, extruded and granulated at a temperature of 190~230℃ and a screw speed of 250~400rpm to obtain the product. During the melt blending process, the epoxy groups of the shell layer of the epoxy functionalized core-shell toughening agent react chemically with the carboxyl groups in the ionomer and the amino groups on the surface of the nano silica to construct an ion-covalent hybrid crosslinking network in situ.

9. The preparation method according to claim 8, characterized in that: The temperature settings for each zone of the twin-screw extruder in step (2) are as follows: Zone 1 190~200℃, Zone 2 205~215℃, Zone 3 215~225℃, Zone 4 220~230℃, Zone 5 220~230℃, and Die head 215~225℃.

Citation Information

Patent Citations

  • Method for preparing novel composite material by using biological plant fiber and ceramic simulating recycle products

    CN108219361A